PHYSICAL AND FUNCTIONAL RESIDENTIAL CHANGES AT TEBET UTARA DALAM STREET CORRIDOR, SOUTH JAKARTA - Budi Heriyanto (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2018)
AbstractThe 1997-2000 economic crises have provoked the rise of a number of speculators alongside the corridor of Jalan Tebet Utara. The function of residential buildings on the left and right sides of the road was developed not only as a residential place but also as a commercial area with the target market of young people. These conditions had an effect on the phenomenon of architectural transformation on the absence of permission for a commercial building that was not in line with the General Spatial Plan of the Government of DKI Jakarta. As a result, the building faces that were originally identical appearedto be diverse, in which one side of the preferred look of the buildingcouldattract visitors. This article discusses the research emphasizing on the problem of building typology and architectural transformation by administering field observation, mapping of building typology and categorizing the transformation of architectural phenomenon. The findings of the study indicate that changes to the commercial-occupancy function are influenced by the increased accessibility which impacted changes on facade and building elements, on the use of building and road lines, andon the sky line environments. Keywords: Residential Changes, Street Corridor, Tebet